STUDI ANALISIS VARIANS RANKING DUA- ARAH FRIEDMAN TERHADAP KOMPETENSI DIMENSI PENGETAHUAN AUDITOR DI KANTOR AKUNTAN PUBLIK JAKARTA - Ratnawati, Ratnawati; Samosir, Perak (MAJALAH ILMIAH WIDYA, 2012)
In conducting the auditing, the auditor should have the competence dimension of knowledge. It can be analyzed through therespondents answers to the statements relating to the competence dimension of knowledge of an auditor. The purpose of this studyis to see if there is a statement to the effect of the respondents answer and whether there is a correlation between the grain statements.The method used analysis of auditor competence dimension of knowledge in performing auditing and other data collected byquestinaires distributed to 30 Public Auditor offices in Jakarta. The result showed that no significant differences from respondentsanswers to the statement items relating to the auditorâs competence of knowledge dimension